Pengaruh Etos Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Bima - Fitri Fitri; Ita Purnama (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
Human resources are the main asset and support for the organization to achieve the goals that have been set. Employees as one of the organizational assets have significant differences from other assets. This is because employees are talented human beings who have creativity and creativity so that they are able to develop optimally and produce everything that is the goal of the organization. This study aims to determine the influence work ethic and work discipline on employee performance at the Bima District Transportation Office. Where research uses associative, namely to find out the independent variables, namely work ethic (X1) and work discipline (X2) on the dependent variable, namely employee performance (Y) with a sampling technique, namely purposive sampling, namely based on the considerations in determining the sample, namely civil servants (PNS) ) in the District Transportation Office. Bima as many as 44 people. 1) there is a partial significant effect of work ethic on performance at the Bima Regency Transportation Service. count value of 5.628. 2) there is no significant effect partially on work discipline on employee performance at the Bima District Transportation Office. The calculated value is 0.545. 3). there is a simultaneous significant effect of work ethic and work discipline on employee performance at the Bima Regency Transportation Service obtained an F count of 36.506